More microcars / Tony Marshall. - Marshall, Tony, 1946- (Sutton, 2001)
Microcars enjoyed a period of popularity during the 20 years following the end of World War II. While motor manufacturers struggled, microcar makers adopted, adapted and exploited the technological advances accelerated by a world in conflict.